2017
DOI: 10.1186/s12885-017-3662-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, chronic conditions and quality of life in elderly hematologic cancer patients: study protocol of a prospective study

Abstract: BackgroundSimilar to most solid tumors, the incidence of hematologic malignancies has been rising. Although the median age at diagnosis is about 70 years, little is known about psychosocial aspects and comorbid conditions in elderly patients with hematologic cancers. The main objectives of our study are to assess the prevalence of psychological distress, chronic conditions, functional disabilities, and quality of life in both elderly hematologic cancer patients aged ≥70 years and an age-matched comparison samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Study participants were offered an allowance of 10€. More information about the 70+ study has been provided by Köhler et al [28].…”
Section: Methodsmentioning
confidence: 99%
“…Study participants were offered an allowance of 10€. More information about the 70+ study has been provided by Köhler et al [28].…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, patient satisfaction with self-monitoring systems through mHealth is dependent on the availability of technical infrastructure, such as mobile networks and bandwidth strength, the ability of health workers to reach rural communities, and the availability of health personnel support. A number of researchers have also argued that the successful implementation of health systems depends on the support health institutions receive in terms of better policies, standards, and strategies, as well as their evaluation and reform [ 1 , 8 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…An mHealth self-monitoring application system will serve as a reminder to timely attend to patients’ health needs. Those living with a chronic disease often give up trying because of anxiety [ 1 , 8 ]. The World Health Organization [ 7 ] showed that inconsistency in drug intake is a major cause of high mortality rates in people with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A more aggressive cancer diagnosis (based on biological and genetic markers) and lack of responsivity to treatment yields a higher risk for psychological distress (especially anxiety) and psychiatric comorbidities. 57 A higher burden of medical comorbidities bears a higher level of emotional distress. 31,58 Rehospitalization after the transplant increases the risk of psychological issues as well.…”
Section: Disease Factorsmentioning
confidence: 99%